IMPLEMENTASI PENGAWASAN PEMERINTAHAN OLEH INSPEKTORAT KABUPATEN NAGAN RAYA PROVINSI ACEH - Rauzatul Ulfah; Ismail Nurdin; Nur Handayani (Jurnal Media Birokrasi, 2020)
The focus of this research is to see the implementation of government supervision carried out by the Inspectorate of Nagan Raya Regency. The research method used is descriptive qualitative method with an inductive approach. Data were collected using the method of observation, interviews, and documentation. Data analysis techniques by reading data, data reduction, data presentation, and data collection. The results showed that the implementation of supervision by the Inspectorate was good enough, seen from 1) the level of reporting by the Inspectorate, 2) measurement of work results; 3) corrections, and corrections to the condition of Human Resources (HR). So it is deemed necessary to develop human resources both in terms of quantity (especially auditors) as well as in terms of quality through education and training or similar activities as well as politics which will be led by the leadership of the Inspectorate of Nagan Raya Regency. In carrying out its duties and functions, only level 2 should be at level 3. Keywords: Inspectorate and Government Supervision